Children with neonatal Hypoxic Ischaemic Encephalopathy (HIE) treated with therapeutic hypothermia are not as school ready as their peers. (3rd July 2021) - Edmonds, Caroline J; Cianfaglione, Rina; Cornforth, Christine; Vollmer, Brigitte
Abstract: Aim: We aimed to determine whether children with neonatal Hypoxic Ischaemic Encephalopathy (HIE) treated with therapeutic hypothermia (TH) differ from their peers on measures of fine motor skills, executive function, language and general cognitive abilities, factors that are important for school readiness. Methods: We compared school readiness in 31children with HIE treated with TH (without Cerebral Palsy; mean age 5 years 4 months) with 20 typically developing children without HIE (mean age 5 years 6 months). Results: Children with HIE scored significantly lower than typically developing children on fine motor skills, executive functions, memory and language. Conclusion: While general cognitive abilities and attainment were in the normal range, our findings suggest those scores mask specific underlying difficulties identified by more focussed assessments. Children with HIE treated with TH may not be as 'school ready' as their typically developing classmates and may benefit from long‐term follow‐up until starting school.